Evaluasi Penerapan PSAK 24 tentang Imbalan Kerja dan Dampaknya pada Laporan Keuangan Perusahaan Sektor Jasa Kesehatan: Studi Kasus pada PT KMU - Wibowo, Ari Iswahyudi; Mappadang, Agoestina; Rahayu, Sri; Indrabudiman, Amir (Penerbit Goodwood, 2024)
Purpose: This study aims to determine the compliance and understanding of PT KMU in implementing PSAK No. 24 of 2018, transparency, and disclosure of information provided by PT KMU to employees regarding the provision of employee benefits, and the impact of the application of PSAK No. 24 of 2018 on PT KMU's financial statements. Research methodology: Qualitative descriptive research was conducted through interviews, observations, and documentation. Results: As a consequence of this study, PT KMU put into effect PSAK 24 of 2018 in compliance with both Indonesian laws and financial accounting standards. PT KMU offers employees full openness and access to information on perks. Applying PSAK No. 24 in 2018 creates deferred tax assets and affects the company's profit margin. Limitations: The limitations of this research are that the interviews with PT KMU informants were conducted simultaneously, and the list of interview questions between informants was the same. Contribution: This research advances our knowledge and comprehension of how to use PSAK 24 of 2018 in compliance with relevant laws and regulations as well as Indonesian Financial Accounting Standards.